2016
DOI: 10.1016/j.jtos.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Intrinsic Mechanisms by Which Mesenchymal Stem Cells Suppress the Immune System

Abstract: Mesenchymal stem cells (MSCs) are a group of fibroblast-like multipotent mesenchymal stromal cells that have the ability to differentiate into osteoblasts, adipocytes, and chondrocytes. Recent studies have demonstrated that MSCs possess a unique ability to exert suppressive and regulatory effects on both adaptive and innate immunity in an autologous and allogeneic manner. A vital step in stem cell transplantation is overcoming the potential graft-versus-host disease, which is a limiting factor to transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 195 publications
1
55
0
1
Order By: Relevance
“…Subsequently, multi investigation have been explored an alternative strategy to produce MSCs. It's reported that secretion of growth factors, miRNAs, and EVs effects on the biological properties of stem cells including stem cell regeneration, differentiation potential, and immunomodulatory roles . Interestingly, the regulatory factors secreted from condition medium of MSCs improved the kidney and myocardial damages in animal model .…”
Section: Mscs Release Extracellular Vesicles As a Novel Approach Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, multi investigation have been explored an alternative strategy to produce MSCs. It's reported that secretion of growth factors, miRNAs, and EVs effects on the biological properties of stem cells including stem cell regeneration, differentiation potential, and immunomodulatory roles . Interestingly, the regulatory factors secreted from condition medium of MSCs improved the kidney and myocardial damages in animal model .…”
Section: Mscs Release Extracellular Vesicles As a Novel Approach Of Cmentioning
confidence: 99%
“…It's reported that secretion of growth factors, miRNAs, and EVs effects on the biological properties of stem cells including stem cell regeneration, differentiation potential, and immunomodulatory roles. 125 Interestingly, the regulatory factors secreted from condition medium of MSCs improved the kidney and myocardial damages in animal model. 126 Last several decades, MSCs immunoregulatory effects such as suppression of T and B cells proliferation, inducing tolerant dendritic cells (DCs), anti-inflamatory cytokines secretion have been demonstrated.…”
Section: Ev Components and Biological Functionsmentioning
confidence: 99%
“…However, the molecular and cellular mechanisms of UMSCs that modulate inflammation and host immune response remain elusive. 5, 6 We previously showed that human UMSCs survived xenograft transplantation, caused low inflammatory responses and successfully corrected corneal clouding defects associated with congenital lysosomal storage disease MPS VII ( Gusb ) and in Lum −/− mice. 25, 27, 30 However, the precise mechanism by which UMSCs suppress the immune system remains elusive.…”
Section: Use Of Umsc and Bmsc For Treating Congenital Corneal Diseases‡mentioning
confidence: 99%
“…Sophisticated gene expression analysis can detect molecular differences, however these are lost upon culturing in vitro [22,23]. MSCs primarily have immunosuppressive roles while fibroblasts can show both pro- and anti-inflammatory roles [24-26]. As MSCs, fibroblasts and myofibroblasts may represent different states of differentiation, other immune cell inputs may play the deciding role in determining the maturation of MSCs and fibrotic potential.…”
Section: Cellular Response To Injury and Cross-regulating Cell-to-mentioning
confidence: 99%